Residual Disease after Operative Hysteroscopy in Patients with Endometrioid Endometrial Cancer Associated with Polyps - Simonsen, Marcelo; Mantoan, Henrique; Faloppa, Carlos Chaves; Kumagai, Lillian Yuri; Badiglian Filho, Levon; Machado, Andrea Guerreiro; Tayfour, Najla Mohamed; Baiocchi, Glauco (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2021)
Objective To evaluate the presence of residual disease in the uterine specimen after hysteroscopic polypectomy or polyp biopsy in patients with endometrioid endometrial cancer (EC).Methods We analyzed a series of 104 patients (92 cases from the Hospital AC Camargo and 12 from the Hospital do Servidor Público Estadual de São Paulo) with polyps that were diagnosed by hysteroscopy, showing endometrioid EC associated with the polyp or in the final pathological specimen. Patients underwent a surgical approach for endometrial cancer from January 2002 to January 2017. Their clinical and pathological data were retrospectively retrieved from the medical records.Results In 78 cases (75%), the polyp had EC, and in 40 (38.5%), it was restricted to the polyp, without endometrial involvement. The pathologic stage was IA in 96 cases (92.3%) and 90 (86.5%) had histologic grade 1 or 2. In 18 cases (17.3%), there was no residual disease in the final uterine specimen, but only in 9 of them the hysteroscopy suggested that the tumor was restricted to the polyp. In 5 cases (4.8%) from the group without disease outside of the polyp during hysteroscopy, myometrial invasion was noted in the final uterine specimen. This finding suggests the possibility of disease extrapolation through the base of the polyp.Conclusion Patients with endometrioid EC associated with polyps may have the tumor completely removed during hysteroscopy, but the variables shown in the present study could not safely predict which patient would have no residual disease.
Keywords: endometrial neoplasm; hysteroscopy; endometrial polyp